Hubungan Tingkat Pengetahuan terhadap Perilaku Swamedikasi Maag Selama Pandemi Covid-19 - Shinta Misdariani Nur; Shoma Rizkifani; Nera Umilia Purwanti (Indonesian Journal of Pharmaceutical Education, 2023)
Many people in the Tumbang Titi area do self-medication, one of which is ulcer disease because it is considered mild and easy to treat without the supervision of health workers. During the COVID-19 pandemic, self-medication became an alternative choice for people in Tumbang Titi District. This study aims to determine the level of knowledge and behavior of self-medication and whether or not there is a relationship between the level of knowledge and behavior of self-medication. This study is an observational study with cross-sectional design. sampling technique used a purposive sampling with considerations based on inclusion and exclusion criteria for 100 community respondents in Tumbang Titi District. Based on the results of the research on the level of knowledge in the community in Tumbang Titi District, the results were in the good category of 29%, 49% good enough and 22% less good. Self-medication behavior was obtained in good category 19%, good enough 57% and not good 24%. The results of the chi-square test of the level of knowledge and behavior of self-medication showed the results showed the value of Sig. of 0.000 (p 0.005). The conclusion of this study is that the level of knowledge has a fairly good category of 49%, self-medication behavior has a good enough category of 57%, there is a relationship between the level of knowledge and self-medication behavior.